El impacto socioeconómico del comercio electrónico internacional en los consumidores colombianos, durante los últimos 10 años (2020)
This document conducts research on the social and economic impact of international electronic commerce on Colombian consumers over the past 10 years. In order to identify what these factors have been, we have researched very recent literature, which has helped us to get closer to the current state of electronic commerce in Colombia and the growth it has had, but we have also detected which social factors have changed. and the economic ones that have managed to generate competitive advantages in some Colombian competitors worldwide. The result of the research is reflected in the current Colombian panorama, where an exponential growth in the matter has been demonstrated, but there are still many gaps to be addressed due to the wide digital gap that exists at a society level and an economic level. On the information presented, some recommendations are given for future lines of study and opens the door to the generation of confidence for those who are curious about the world of digital transformation.